Qualitative research in action - May, Tim, 1957- (London : SAGE, 2002)
Rather than being a how-to book, this volume examines the ideas and practices of qualitative research in terms of their applicability for an understanding and explanation of the place of qualitative research in the social sciences.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Qualitative research; Social sciences -- Research